Arctic pathways of Pacific Water: Arctic Ocean Model Intercomparison experiments. Issue 1 (8th January 2016) - Aksenov, Yevgeny; Karcher, Michael; Proshutinsky, Andrey; Gerdes, Rüdiger; de Cuevas, Beverly; Golubeva, Elena; Kauker, Frank; Nguyen, An T.; Platov, Gennady A.; Wadley, Martin; Watanabe, Eiji; Coward, Andrew C.; et al.
Abstract: Pacific Water (PW) enters the Arctic Ocean through Bering Strait and brings in heat, fresh water, and nutrients from the northern Bering Sea. The circulation of PW in the central Arctic Ocean is only partially understood due to the lack of observations. In this paper, pathways of PW are investigated using simulations with six state‐of‐the art regional and global Ocean General Circulation Models (OGCMs). In the simulations, PW is tracked by a passive tracer, released in Bering Strait. Simulated PW spreads from the Bering Strait region in three major branches. One of them starts in the Barrow Canyon, bringing PW along the continental slope of Alaska into the Canadian Straits and then into Baffin Bay. The second begins in the vicinity of the Herald Canyon and transports PW along the continental slope of the East Siberian Sea into the Transpolar Drift, and then through Fram Strait and the Greenland Sea. The third branch begins near the Herald Shoal and the central Chukchi shelf and brings PW into the Beaufort Gyre. In the models, the wind, acting via Ekman pumping, drives the seasonal and interannual variability of PW in the Canadian Basin of the Arctic Ocean. The wind affects the simulated PW pathways by changing the vertical shear of the relative vorticity of the ocean flow in the Canada Basin. Key Points: Pathways of the Arctic Pacific Water are investigated in ocean models Variability of the Pacific Water due to wind is examined Mechanisms of the Pacific Water variability are suggested